Intergenerational Digital Storytelling for Inuvialuit Cultural Heritage Preservation - Sasso Annunziata, Rebecca; Farnel, Sharon; Shiri, Ali (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2026)
This paper provides an overview of mobile storytelling applications developed for and by Indigenous communities. It identifies and examines a variety of mobile applications to support Indigenous cultural and linguistic heritage. These applications include those reported in the literature as well as those available in application stores. The review provides a detailed overview of the mobile application interface functions and features, including recording capabilities, language-related features, accessibility, content categorization, and geolocation. Based on the review, this paper provides a set of design recommendations for developing mobile applications for Indigenous communities, including for Indigenous protocols, voices, and community needs.